Comprehensive Analysis of Therapeutic Strategies for Mycoplasma pneumoniae Infections: A Global and European Review of Current Antibiotic Treatment Standards in Paediatric and Adult Populations in an Era of Increasing Antimicrobial Resistance - Krystek, Klaudia; Botto, Zofia; Swojnóg, Marzena; Felisiak, Patrycja; Reizer, Barbara; Kowalczyk, Dominika; Śliwa, Zofia; Ślazyk, Dominik Andrzej (Quality in Sport, 2026)
Background. Mycoplasma pneumoniae infections remain a significant clinical challenge, particularly in the paediatric population, where they constitute a common cause of community-acquired pneumonia (CAP). The absence of a cell wall results in intrinsic resistance to beta-lactam antibiotics, necessitating the use of antimicrobials targeting intracellular processes. In the post-pandemic period, a resurgence of M. pneumoniae infections has been observed, partly attributed to an “immunity gap” following non-pharmaceutical interventions. At the same time, macrolide-resistant M. pneumoniae (MRMP) has become an increasing concern, especially in Asia and increasingly in Europe, significantly influencing therapeutic strategies. Aim. To review current antibiotic treatment standards for Mycoplasma pneumoniae infections in children and adults, with particular emphasis on macrolide resistance, regional epidemiology, and practical clinical management of CAP of suspected mycoplasmal aetiology. Material and methods. This narrative review analysed contemporary literature published primarily between 2010 and 2025. Data sources included clinical guidelines for CAP in adults and children, systematic reviews and meta-analyses on MRMP, primary studies on resistance mechanisms (23S rRNA mutations, L4/L22 alterations, resistance emergence during therapy), and studies evaluating doxycycline safety in children. Peer-reviewed articles indexed in PubMed and PubMed Central were included. The synthesis was structured according to patient age, disease severity, geographical region, and therapeutic decision pathways. Results. Available evidence indicates increasing global prevalence of MRMP, with marked regional differences. Macrolides remain first-line therapy in many settings; however, treatment failure rates are higher in regions with elevated resistance. Doxycycline and fluoroquinolones represent effective alternatives, with growing evidence supporting doxycycline safety in paediatric populations. Escalation of therapy after 48–72 hours of non-response is a key component of effective management, particularly in severe or refractory cases. Conclusions. Mycoplasma pneumoniae remains a major cause of CAP in both children and adults. Rising macrolide resistance necessitates region-specific treatment strategies, careful clinical reassessment, and judicious antibiotic selection. Updated management algorithms incorporating resistance patterns and timely therapy escalation are essential to optimise outcomes and support antibiotic stewardship.